2019
DOI: 10.1080/10242694.2019.1661218
|View full text |Cite
|
Sign up to set email alerts
|

Military Expenditures and Income Inequality Evidence from a Panel of Transition Countries (1990-2015)

Abstract: This paper contributes to the literature on military spending by analyzing the relationship between military spending and income inequality in a panel of transition economies over the period 1990-2015. In particular, we exploit three different measures of military expenditures: (i) the military spending in absolute terms; (ii) the military expenditures per capita; (iii) the military burden, namely the ratio between military expenditure and GDP. Findings highlight a positive relationship between military expend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 72 publications
3
13
0
Order By: Relevance
“…Others argue that military spending may exacerbate income inequality if (1) workers in military‐related industries are paid better than those in other sectors, (2) there is an income disparity within the military and ‐related industries between less‐skilled labor (e.g. low‐rank soldiers) and high‐skilled research and development personnel, and (3) military spending crowds out social expenditures, such as education, health, and social transfers (Ali, 2007; Apostolakis, 1992; Biscione & Caruso, 2019; Fan, Wei, & Coyte, 2018; Graham & Mueller, 2019; Kentor, Jorgensen, & Kick, 2012; Shin, 2020). Another group of studies reported a mixed or no significant relationship between military spending and income inequality.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Others argue that military spending may exacerbate income inequality if (1) workers in military‐related industries are paid better than those in other sectors, (2) there is an income disparity within the military and ‐related industries between less‐skilled labor (e.g. low‐rank soldiers) and high‐skilled research and development personnel, and (3) military spending crowds out social expenditures, such as education, health, and social transfers (Ali, 2007; Apostolakis, 1992; Biscione & Caruso, 2019; Fan, Wei, & Coyte, 2018; Graham & Mueller, 2019; Kentor, Jorgensen, & Kick, 2012; Shin, 2020). Another group of studies reported a mixed or no significant relationship between military spending and income inequality.…”
Section: Review Of Literaturementioning
confidence: 99%
“…The discussion in the empirical papers on the economic impact of military spending started with the Benoit (1978). There are many papers which have examined nexus between military expenditure and economic growth in the world (Dune and Uye, 2008;Malizard, 2010;Alptekin and Levine, 2012;Hou and Chen, 2013;Tiwari and Shahbaz, 2013;Furuoka et al 2014;Dimitraki and Menla-Ali, 2015;Compton and Paterson, 2015;Pan et al 2015;Manamperi, 2016;Cevik and Ricco, 2017;Phiri, 2017;Markowski et al 2017;Smith, 2017;Emmanouilidis and Karpetis, 2018;Biscione and Caruso, 2019;Dimitraki and Win, 2020). Dunne and Uye (2008) analyzed 102 empirical papers that have evaluated the nexus between military expenditure and economic growth and their findings confirmed that a positive relationship is identified in 19% of the observed studies.…”
Section: Literature Reviewmentioning
confidence: 88%
“…On the other hand, if the system was driven by economic shocks, the observed correlation would have a positive character. Biscione and Caruso (2019) analyzed military expenditure in transition countries over the period 1990-2015 and highlighted that military expenditure could have a detrimental effect on the national economy. Khalid and Habimana (2019) analyzed military spending and economic growth in Turkey for the period 1961-2014.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A null result may call into question the model specification of Coutts et al ( 2019 ). Biscione and Caruso ( 2021 ) found that the once-lagged military expenditure–total government expenditure ratio has no significant effect on current health expenditure in a sample of 26 transition countries over the period 1990–2015. In spite of their inconclusive empirical evidence, Biscione and Caruso ( 2021 ) contributed to the “crowding-out effect” debate by their attempting investigating a delayed impact.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Coutts et al ( 2019 ) found that military burden has no significant impact on health burden in 18 countries in the Middle East and North Africa region over the period 1995–2011. Biscione and Caruso ( 2021 ) found that the once-lagged military expenditure–total government expenditure ratio has no significant effect on current health expenditure in a sample of 26 transition countries over the period 1990–2015. These studies differ widely in method and focus, and their empirical results point to rather different conclusions.…”
Section: Introductionmentioning
confidence: 99%